Edukasi Peluang dan Tantangan Pemuda di Era Society 5.0 bagi Mahasiswa Sekolah Tinggi Ekonomi Islam Tiara, Yayasan Napala Indonesia, Bogor, Jawa Barat (Neolectura, 2022)
This activity aims to provide education regarding the opportunities and challenges of youth in facing the Society 5.0 era. This service activity is carried out in the form of a seminar which is open to the public but in practice it is required for partner students. Partners in this activity are Tiara Islamic Economics College, Napala Indonesia Foundation, Bogor, West Java. The enthusiasm of the participants in this activity was very high. This can be seen from the activeness and consistency of the number of participants, which from the beginning to the end of the activity did not show a significant decrease. This two-hour online activity through the online meeting platform Zoom Meeting shows how much it is necessary for youth to be educated in facing the challenges and opportunities in the era of Society 5.0. In this activity, it is only limited to opportunities and challenges in the scope of the world of education and the economic sphere that exist in the era of Society 5.0.